THE MATERIALS AND ADDITIVES APPLICATION FOR THE MODIFICATION OF TECHNOLOGICAL AND OPERATIONAL PROPERTIES OF REPAIR COMPOUNDS FOR SPECIAL PURPOSES IN THE REPAIR OF BUILDINGS AND ENGINEERING STRUCTURES ON THE TRANSPORT - Pshinko, O. M.; Krasnyuk, O. V.; Gromova, O. V.; Palii, V. V. (Science and Transport Progress, 2008)
In the article one of directions of creation of repair material with the set technological and operational properties by means of use of modifying additives of the directed or multifunctional action is considered. The requirements to repair compositions of special purpose for different conditions of operation of a construction are established and the categories of materials for repair are separated. The review of modern synthetic additives and ground-additives for modifying the properties of repair compositions of special purpose is carried out.